Mathematical reflective thinking type of error on Newman’s error analysis / Muntazhimah, Sufyani Prabawanto and Turmudi - -, Muntazhimah; Prabawanto, Sufyani; -, Turmudi (Universiti Teknologi MARA, 2023)
A body of literature has revealed that Mathematical reflective thinking could improve student achievement and success in mathematics learning. However many students make errors in completing mathematics reflective thinking problems. Hence, this qualitative study sought to explore the errors of pre-service mathematics teachers in completing the reflective thinking ability test using Newman's Error Analysis (NEA). A total of twenty-four of the 4th-semester students of mathematics education or preservice mathematics teachers participated in the study. The methods used in this study were tests, interviews, and triangulation. The results showed that pre-service mathematics teachers made technical, conceptual, procedural, and interpretation errors. In terms of NEA, the error started from the comprehension stage, transformation, and process skills to encoding. Further research should design learning that can stimulate and improve the mathematical reflective thinking ability of pre-service mathematics teachers in order to reduce errors of mathematical reflective thinking processes.